Potassium Sulfate Supplementation with Elevated Electrical Conductivity Was Unproductive for Hydroponic Strawberry at the Original Yamazaki Nutrient Solution Nitrogen Level - Jonathan Ries; Qingwu Meng; Yujin Park (HortScience)
The production of strawberries (Fragaria ×ananassa) in hydroponic systems has been increasing. In hydroponic systems, precise nutrient management is crucial for optimal plant growth and fruit production. Among essential elements, potassium (K) is a key nutrient that affects fruit yield and quality in fruiting crops. The objective of this study was to investigate whether increasing the K concentration in the Yamazaki strawberry nutrient solution could enhance plant growth, fruit yield, and fruit quality in hydroponic strawberries. Bare-root plants of strawberry ‘Monterey’ and ‘San Andreas’ were planted in a deep water culture hydroponic system and grown with initial K concentrations of 117, 194, 271, and 348 mg·L−1 under the same initial nitrogen concentration of 77 mg·L−1. As the K concentration increased from 117 to 348 mg·L−1, the nutrient solution electrical conductivity increased from 1.0 to 1.9 dS·m−1. The experiment was conducted inside an indoor vertical farm at a 23 °C air temperature with an extended photon flux density (400–750 nm) of 350 µmol·m−2·s−1 under an 18-hour photoperiod. Increasing the K concentration from 117 to 348 mg·L−1 had minimal effects on plant growth characteristics of both cultivars, although root dry mass of ‘Monterey’ increased linearly with increasing K. Increasing the K concentration from 117 to 348 mg·L−1 did not affect the total fruit number or total fruit fresh mass of ‘Monterey’, but for ‘San Andreas’, it reduced the total fruit number by 34% and total fruit fresh mass by 45%. Additionally, increasing the K concentration from 117 to 348 mg·L−1 reduced the individual fruit mass, fruit length, and fruit diameter and increased titratable acidity in both cultivars. These results indicate that increasing the K concentration in the Yamazaki strawberry nutrient solution did not benefit plant growth, fruit yield, or fruit quality of the hydroponically grown strawberries ‘Monterey’ or ‘San Andreas’.